UJI DAYA HAMBAT ANTIJAMUR BUAH BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP PERTUMBUHAN Pityrosporum ovale PENYEBAB KETOMBE - Marliana Marliana; Ulfayani Mayasari (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
One of the plants that can be used as medicine is Wuluh starfruit (Averrhoa bilimbi L.). Starfruit fruit has antipyretic, antiseptic, anti-inflammatory properties, treats coughs and treats rashes. Wuluh starfruit (Averrhoa bilimbi L.) contains chemical compounds of flavonoids, saponins, alkaloids, and tannins. This study aims to determine the anti-fungal inhibition of star fruit (Averrhoa bilimbi L.) on the growth of Pityrosporum ovale which causes dandruff. The method used to obtain the extract of starfruit (Averrhoa bilimbi L.) through a maceration process using ethanol 96% solvent. The anti-fungal inhibition test used the agar diffusion method by sticking disc paper on the media that had been grown by the fungus Pityrosporum ovale. The results of phytochemical screening showed that the fruit of starfruit (Averrhoa bilimbi L.) contained flavonoid, alkaloid, tannin and saponin compounds. The resulting inhibitory power was indicated by the formation of a clear zone at each concentration of 20%, 40%, 60%, 80%, and as a comparison, a positive control of 10% ketonazole was made. The average diameter obtained was 6.26 mm, 7.09 mm, 7.57 mm, 8.07 mm, and 17.29 mm. Based on the results of the study, it was concluded that the extract of starfruit (Averrhoa bilimbi L.) had an inhibitory power against the growth of Pityrosporum ovale.